Effectiveness of Implementing a Directing Flow System in Increasing the Number of Clinic Visitors UPT Lab. Herbal Materia Medica Batu - Yermi Bryan Suwandani; Ardi Bastian (Universitas STRADA Indonesia, 2019)
Low number of patient visits at the UPT Lab Clinic. Herbal Material Medica Stone. The high number of visits to the Herbalmart unit as a herbal medicine sales unit is inversely proportional to the number of visits to the Clinic unit. This study aims to analyze differences in the number of clinic visitors before and after the implementation of the Directing Flow System visitor flow system at the UPT Lab. Herbal Material Medica Stone. This research method is a pre-experiment one group pre-test-posttest design with a quantitative approach. The sample in this study was 30 days before and after implementing the intervention. The statistical test used is T – Paired Test. The statistical test results obtained a Sig value. (2-tailed) is 0.000 < 0.05, which means that there is a difference in the number of clinic visitors before and after the implementation of the Directing Flow System visitor flow system towards increasing the number of visitors at the UPT Lab. Herbal Material Medica Batu. It is recommended that the Batu Herbal Materia Medica Lab UPT consistently implement the Directing Flow System so that clinic visits continue to increase.